Lower limb paediatric trauma with bone and soft tissue loss: Ortho-plastic management and outcome in a major trauma centre. Issue 7 (July 2020) - Messner, J; Harwood, P; Johnson, L; Itte, V; Bourke, G; Foster, P
Highlights: Early intervention providing adequate debridement, skeletal stabilisation and early soft-tissue cover by an ortho-plastic consultant-led team delivers acceptable outcomes in severe lower limb paediatric trauma minimising the risk of infection and non-union. The ongoing impact of these injuries on quality of life and psychological function is significant. This should be taken into account when caring for such patients and designing systems for their management. This study reports surgical and patient reported functional and psychological outcomes in paediatric patients with severe open lower limb fractures. We review our current practice, describe a treatment algorithm and evaluate our multidisciplinary approach. Abstract: Aim: We examined the management and outcome of patients suffering complex paediatric lower limb injuries with bone and soft tissue loss. Method: Patients were identified from our prospective trauma database (2013-2018). Inclusion criteria were age (<18 years) and open lower-limb trauma. We assessed severity of soft tissue and/or bone loss, fracture complexity, surgical techniques and time to surgery. Paediatric quality of life and psychological trauma impact scores (HRQOL and CRIES), Ganga Hospital Injury Severity score (GHISS), union and complication rates were measured. Results: We identified 32 patients aged between 4 and 17 years. Twenty-nine patients had open tibia fractures including 14 patients with bone loss, one patient had an open femur fracture, one patient an open talus fracture and one an open ankle fracture with dorsal degloving. Thirty injuries were classified intra-operatively as Gustilo IIIB (or equivalent) and two injuries as Gustilo IIIC. In 10 patients primary skin closure was achieved by acute shortening following segmental bone loss. Twenty-two patients required soft tissue coverage: 17 free vascularised flaps, two fascio-cutaneous flaps and three split skin grafts were used. Two patients required vascular repair. Soft tissue coverage was achieved within 72 hours in 26 patients (81%) and within a week in 30 patients (94%). The surgical techniques applied were: circular fine wire frame (19), monolateral external fixator (4) and open reduction internal fixation (8). Median follow up time was 18 (7-65) months. Paediatric quality of life scores were available in 30 patients (91%) with a median total score of 77.2 out of 100. The psychological trauma impact scores showed one in three patients was at risk of developing post-traumatic stress symptoms (PTSD). The GHISS scores ranged from 6-13. All fractures went on to unite over a median time of 3.8 (2-10) months. Three patients (9%) had major complications; two flap failures requiring revision, one femur non-union requiring revision fixation. Conclusion: Limb salvage and timely fracture union is possible in children with complex lower limb trauma. Early intervention providing adequate debridement, skeletal stabilisation and early soft-tissue cover including the option of free microvascular reconstruction in small children when required, delivers acceptable outcomes. A multidisciplinary team approach including clinical psychologists to address the psychological impact of trauma provides optimal holistic care for these children and adolescents. Therefore, treatment for these patients should only be performed in paediatric major trauma centres.